Hydrodynamic parameters affecting flow-accelerated corrosion in elbows - Moon, Seongin; Lee, Jong-Yeon; Kim, Kyung-Mo; Han, Soon-Woo; Lee, Gyeong-Geun; Maeng, Wan-Young; Kim, Dong-Jin; Jo, Hyunseung; Kim, Shin Hyuk (Nuclear engineering and technology, 2025)
Flow-accelerated corrosion (FAC) is a serious degradation mechanism affecting carbon-steel piping in the secondary coolant systems of nuclear power plants. Many researchers have investigated the correlation between wall thinning and hydrodynamic parameters; however, their relationship remains unclear. In this study, the hydrodynamic parameters influencing FAC in elbow sections were investigated for identifying the locations highly susceptible to FAC. Accelerated FAC tests and computational fluid dynamics (CFD) analyses were conducted on a specimen containing elbow sections. The results revealed that the side of the elbow pipe was the most susceptible to FAC because it experienced the most severe wall thinning. The velocity and vorticity vectors obtained from the CFD analysis were decomposed into axial, circumferential, and radial components within a cylindrical coordinate system to evaluate their effects. We found that all velocity and vorticity components contribute to the rate of wall thinning induced by FAC. Therefore, a combination of velocity and vorticity components should be used as hydrodynamic parameters to characterize FAC-induced wall thinning. Specifically, the circumferential velocity and axial vorticity were identified as dominant parameters influencing FAC in the elbows.